Geochemical controls on mobilization of metals from a 100-year-old waste rock pile and implications for selection of cover amendments. (1st March 2023) - Doyle, Sarah; Figueroa, Linda; Heinze, David
Abstract: Reclamation of mine waste rock piles typically consists of constructing a cover with amendments to improve conditions for vegetation. However, cover amendments have potential to mobilize metals in waste by introducing new chemicals and altering pH and redox conditions. This study evaluates metal phases in a 100-year-old waste rock pile with high metals content (3.5% lead by weight, 0.8% zinc, and 0.75% copper) and the potential for these metals to be mobilized by several cover materials and amendments (topsoil, spent brewery grain, biochar, compost, commercial soil media, and phosphate). Laboratory testing indicates that metals have weathered from their initial metal sulfide phases (galena, sphalerite, chalcopyrite), and are now also present as sulfates, phosphates, carbonates, and phases associated with manganese/iron oxides. Sequential extraction tests demonstrated that the largest extractable fraction of metals is associated with manganese/iron oxides (37% of lead by weight, 22% of copper, and 26% of zinc), suggesting an environmental risk should geochemically reducing conditions develop and mobilize metals in the pile after cover construction. Testing of specific cover materials demonstrated that metals mobilization also occurs from low pH (as with spent brewery grain), formation of stable aqueous metal–organic complexes (as with spent brewery grain and compost), and ligand exchange (as with phosphate amendment). Results of this study demonstrate the importance of identifying metal phases present in a waste rock pile prior to selecting cover amendments. Highlights: Metal phases were studied in historical waste rock for a polymetallic sulfide mine. Cover amendments were tested to evaluate their potential to mobilize metals. Metals release will occur should geochemically reducing conditions develop. Organic amendments formed stable aqueous metal–organic complexes. Metal phases in waste should be identified prior to selection of cover materials.